Bond-slip performance of water cooling steel-reinforced high-strength concrete after high temperature - Shaohua Pang; Yuming Huang; Zongping Chen; Peihuan Ye (Case Studies in Construction Materials, 2023)
The degradation of bond-slip behavior between steel and concrete after a fire is one of the potential causes of building collapse. In contrast, water cooling is the most commonly used method for extinguishing fires. This paper presents an experimental study on the bond-slip performance of water-cooled steel-reinforced high-strength concrete (SRHC) after exposure to high temperatures. A total of 19 SRHC specimens were tested using push-out experiments to characterize the load-slip curves. The study also discusses the effects of key parameters, including maximum temperature, concrete strength, constant temperature duration, and anchorage length of the steel section, on bond-slip performance. The results indicate that the critical point for degradation of high-strength concrete due to water cooling is 400 °C. As the temperature increases, the bond strength and shear stiffness of the specimens decrease, while the energy dissipation capacity increases. Furthermore, this study develops a constitutive model for water-cooled bond-slip behavior in SRHC and proposes formulas for ultimate bond strength and residual bond strength.